The Association of the Sequence of Immunotherapy With the Survival of Unresectable Pancreatic Adenocarcinoma Patients: A Retrospective Analysis of the National Cancer Database - Amin, Saber; Baine, Michael J.; Meza, Jane L.; Lin, Chi (Frontiers in Oncology, 2020)
Background: Immunotherapy has shown great success in various malignancies. However, its efficacy in pancreatic ductal adenocarcinoma (PDAC) remains a challenge. The lack of understanding about the timing of immunotherapy with other standard-of-care cancer treatments may be one of the causes. The objective of this study is to investigate the impact of the timing of immunotherapy with chemotherapy and radiation therapy (RT) on the overall survival (OS) of PDAC patients who did not receive surgical resection of the primary site. Materials and methods: Patients with pancreatic adenocarcinoma who did not receive surgical resection of the pancreatic tumor were identified from the National Cancer Database (NCDB). Cox proportional hazard models were employed to compare the OS between patients who received immunotherapy with chemotherapy or RT with a different sequence of treatment. The multivariable analysis was adjusted for age of diagnosis, race, sex, place of living, income, education, treatment facility type, insurance status, and year of diagnosis. Results: In total, 705 patients received chemotherapy and immunotherapy, while 226 received radiation therapy and immunotherapy. In the multivariable analysis, there was no significant difference in the OS of patients who started immunotherapy 31-90 days before the start of chemotherapy with a hazard ratio (HR) of [HR:1.057 (CI: 0.716-1.56; p <0.781)] and patients who started immunotherapy 91-180 days before the start of chemotherapy [HR: 0.900 (CI: 0.584-1.388; p <0.635)] compared to patients who started chemotherapy and immunotherapy within 30 days of each other. There was also no significant difference in the OS of patients who started RT> 30 days before the start of immunotherapy [HR: 0.636 (CI: 0.346-1.171; p <0.146) and patients who started immunotherapy > 30 days before the start of RT [HR: 0.660 (CI: 0.328-1.329; p <0.246)] compared to patients who started RT and immunotherapy within 30 days of each other. Conclusion: The sequence of immunotherapy with chemotherapy or RT was not associated with improved OS. Future studies with a larger subgroup sample size investigating the impact of the timing of immunotherapy with chemotherapy and RT on the OS of PDAC patients who did not receive surgical resection of the pancreatic tumor are needed.